Triggers for innovative disruption In South African secondary schools - Iyer, Aveshnee (My University, 2018)
The public schooling system across the world, is currently based on standardisation and efficiencies of a factory model, given the influence of the industrialisation era. Larger systemic challenges posed say that the current educational system operates on outdated definitions of intelligence and the learning process. Whilst learning systems are being redefined conceptually, how we respond and integrate technology into this interpretation becomes a key aspect of change required in the education sector. By reviewing and learning from change we start to understand the impacts and opportunities for disruptive innovation to the South African secondary school landscape. This study will look at the triggers for disruption in the education sector and explore whether disruptive innovation can contribute to an approach for improving performance in the South African secondary education sector. The research will assess the enablers and barriers, and create a body of knowledge for application to the South African context. Stakeholders interested in this type of research include public education policy makers, educators, provincial and national government, education theorists and think tanks. In chapter four the data from the qualitative research is presented and in chapter five the data is explored wherein more analysis is provided. Chapter six talks to recommendations, policy changes and measurements to support.
A research report submitted to the Wits Business School in the University of the Witwatersrand, in partial fulfilment of the requirements for the degree of Master of Management in the field of Innovation Studies, Johannesburg, 2018
Keywords: Educational innovations--South Africa; Educational change.